Analisa Sifat Mekanik Paduan Serat Ijuk Dan Serat Jerami Sebagai Pengganti Serat Sintetis Pada Body Mobil - Laily Ulfiyah; Faizatur Rohmah; Tristiandinda Permata; Yopi Ariyanto (Rekayasa Material, Manufaktur dan Energi, 2021)
The manufacture of natural fiber composites was carried out to determine whether the composite from a combination of palm fiber and straw fiber was feasible as a substitute for synthetic fiber composites used for electric car bodies at State Polytechnic of Madura. This research was conducted with variations in the ratio of 100% palm fiber, 100% straw fiber, 1: 2, 2: 1 and 1: 1. Testing of composite material alloys was carried out by testing the impact test, tensile test, and testing the material on the cars body prototype. Based on the test results on the composite and prototype, it was known that the 100% variation of palm fiber has the highest modulus of elasticity, which was 499.09 N / mm2, while the 2: 1 variation has the highest toughness value, which was 14.4.10-3J / mm2, and the results of the crash test was carried out to get a speed of 3.84 m / s, the body surface only experienced cracks, without major damage.